Serum Acylated Ghrelin Is Negatively Correlated with the Insulin Resistance In the CODING study - Amini, Peyvand; Wadden, Danny; Cahill, Farrell; Randell, Edward; Vasdev, Sudesh; Chen, Xihua; Gulliver, Wayne; Zhang, Weizhen; Zhang, Hongwei; Yi, Yanqing; Sun, Guang (PLoS ONE, 2012)
Objective: Ghrelin is a 28-amino acid orexigenic peptide synthesized mainly in the stomach. Acute administration of ghrelin has been found to decrease insulin secretion. However, little data is available regarding whether ghrelin contributes to the long-term regulation of insulin resistance at the population level. The aim of this study is to investigate the association between circulating ghrelin and insulin resistance in a large population based study. Design: A total of 2082 CODING study (Complex Diseases in the Newfoundland population: Environment and Genetics) subjects were assessed. Subjects were of at least third generation Newfoundland descent, between the ages of 20 and 79 years, and had no serious metabolic, cardiovascular, or endocrine diseases. Ghrelin was measured with an Enzyme Immunoassay method. Insulin and fasting glucose were measured by Immulite 2500 autoanalyzer and Lx20 clinical chemistry analyzer, respectively. Homeostatic Model Assessment of beta cell function (HOMA-beta) and Insulin Resistance (HOMA-IR) and Quantitative Insulin-sensitivity Check Index (QUICKI) were used for measurement of insulin resistance. Results: Partial correlation analyses showed a significant negative correlation between circulating ghrelin and insulin level and insulin resistance in the entire cohort and also in men and women separately. The aforementioned correlation was independent of age, percentage of trunk fat and HDL-cholesterol. According to menopausal status, only pre-menopausal women revealed negative correlations. Conclusion: Our results suggest that except for postmenopausal women, high circulating ghrelin level is associated with lower insulin resistance in the general population. Multidisciplinary Sciences SCI(E) 7 ARTICLE 9 null 7